Pengaruh Struktur Kepemilikan dan Free Cash Flow terhadap Kebijakan Dividen - Nadila, Celsya; Taqwa, Salma (Jurnal Nuansa Karya Akuntansi, 2024)
This study purpose to examine how the effect of ownership structure and free cash flow on dividend policy. The population in this study are manufacture companies listed on Indonesia Stock Exchange in 2018-2022. The research uses purposive sampling technique to obtain reearch samples. The data analysis technique in this study used multiple linear regression analysis using the SPSS 22 program. The results showed tht Institutional Ownership, Foreign Ownership,had signidicant positif effect on dividend policy, while Free Cash Flow negative effect on dividend policy. For further research, it is expected to choose other variables that have effect on dividend policy.